Religious Moderation in Islamic Boarding Schools Against Strengthening Democracy in Tabagsel, North Sumatra - Susanti Hasibuan; Zufina Zulfina; Ian Alpian; Yenny Batubara (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Religious moderation is present as a solution for understanding the extreme right and extreme left, especially regarding the massive movement of radicalism which, if allowed to continue, will lead to acts of terrorism. For this reason, it is necessary to carry out Focus Group Discussions which aim to have mutual dialogue and exchange of ideas between service teams and teaching staff at Islamic boarding schools so that educators become pioneers and partners of the government in spreading the notion of religious moderation. This service was carried out by two Islamic boarding schools in TABAGSEL, namely the Al-Ansor Padangsidempuan Islamic Boarding School and the Mustafawiyah Mandailing Natal Islamic Boarding School. This service uses the PAR method with steps; Conducting a needs analysis for understanding moderation for teaching staff, namely ustadz/ustadzah at the Musthofawiyah Islamic Boarding School in Mandailing Natal district and Al-Anshor Islamic Boarding School in Padang Sidempuan City, by conducting Focus Group Discussions with STAIN Mandailing Natal lecturers. The purpose of carrying out this FGD is to find out the understanding of ustadz/ustadzah regarding religious moderation. Form participants and engage in mentoring that presents resource persons as sources of information. The results that can be received after carrying out the FGD are that the ustadz/ustadzah have often heard the word religious moderation. It's just that they don't know clearly about religious moderation in depth. The implementation of this community service was highly appreciated by both the FGD participants as well as the principals and foundations because it was considered to broaden the horizons of the teaching staff at the pesantren. Keywords: Religious Moderation, Islamic Boarding School, ustadz/ustadzah